HIGH-PERFORMANCE AFFINITY CHROMATOGRAPHY AND THE ANALYSIS OF DRUG INTERACTIONS WITH MODIFIED PROTEINS: BINDING OF GLICLAZIDE WITH GLYCATED HUMAN SERUM ALBUMIN - Matsuda, Ryan (2011)
This study used high-performance affinity chromatography (HPAC) to examine the binding of gliclazide (i.e., a sulfonylurea drug used to treat diabetes) with the protein human serum albumin (HSA) at various stages of modification due to glycation. Frontal analysis conducted with small HPAC columns was first used to estimate the number of binding sites and association equilibrium constants (K(a)) for gliclazide with normal HSA and glycated HSA. Both normal and glycated HSA interacted with gliclazide according to a two-site model, with a class of high affinity sites (average K(a), 7.1-10 × 10(4) M(−1)) and a group of lower affinity sites (average K(a), 5.7-8.9 × 10(3) M(−1)) at pH 7.4 and 37°C. Competition experiments indicated that Sudlow sites I and II of HSA were both involved in these interactions, with the K(a) values for gliclazide at these sites being 1.9 × 10(4) M(−1) and 6.0 × 10(4) M(−1), respectively, for normal HSA. Two samples of glycated HSA had similar affinities to normal HSA for gliclazide at Sudlow site I, but one sample had a 1.9-fold increase in affinity at this site. All three glycated HSA samples differed from normal HSA in their affinity for gliclazide at Sudlow site II. This work illustrated how HPAC can be used to examine both the overall binding of a drug with normal or modified proteins and the site-specific changes that can occur in these interactions as a result of protein modification.